Tinjauan Hukum Terhadap Pengguna Aplikasi Whatsapp Business Terkait Kesepakatan Atau Transaksi Jual - Beli Online - Lalu M. Ansori; I Made Dedy Priyanto (KOLONI, 2024)
Down syndrome sufferers often experience speech acts that are difficult to interpret. Therefore, researchers will observe the level of locution, illocution and perlocution of Down syndrome sufferers who attend SLB Tunas Bangsa, Blitar Regency. In people with Down syndrome there is weakness in speech acts. They have difficulty conveying ideas. Communication problems experienced by children with Down syndrome include difficulty in making sounds and using language rules. Many children with Down Syndrome experience developmental delays in many aspects including understanding speech in communication. In this research, researchers found a breakthrough in researching locutions, illocutions, perlocutions or speech acts of Down syndrome sufferers so that later there will be improvements in the speech teaching of Down syndrome sufferers. This research uses a qualitative paradigm or approach. With this descriptive research, it is hoped that it can explain the application and describe locutions and illocutions. perloksi in the conversation of children suffering from Down syndrome at SLB Tunas Bangsa, Blitar Regency. In this research, researchers used a purposive sampling technique, namely by determining a number of informants with certain criteria. Data collection techniques in this research used observation, interviews and documentation from Down syndrome sufferers who attended SLB Tunas Bangsa, Blitar Regency. The results of this research show that Down syndrome sufferers have an IQ below the average of normal people, so they have deficiencies in locutionary, illocutionary and perlocutionary speech acts. If they fail to produce clear speech and experience deficiencies in making illocutionary and perlousional responses to the speech partner. Therefore, there is a need for special measures and special training for children with Down syndrome to improve locutionary, illocutionary and perlocutionary skills